Transcatheter aortic valve deployment influences neo‐sinus thrombosis risk: An in vitro flow study. Issue 5 (9th July 2019) - Madukauwa‐David, Immanuel David; Sadri, Vahid; Kamioka, Norihiko; Midha, Prem A.; Raghav, Vrishank; Oshinski, John N.; Sharma, Rahul; Babaliaros, Vasilis; Yoganathan, Ajit P.
Abstract: Objectives: We investigated the impact of (transcatheter heart valve) THV expansion at the level of the native annulus and implant depth on valve performance and neo‐sinus flow stasis. Background: Flow stasis in the neo‐sinus is one of the identified risk factors of THV thrombosis. Methods: A 29 mm CoreValve and 26 mm SAPIEN 3 were deployed under different expansions (CoreValve, SAPIEN 3) and implant depths (CoreValve) within a patient‐derived aortic root in a pulse duplicator. Fluorescent dye was injected during diastole into the neo‐sinus and imaged over 20 cardiac cycles. Washout times were computed as a measure of flow stasis for each deployment. Results: The 10% CoreValve under‐expansion improved neo‐sinus washout over full expansion by 8% ( p < .001), and higher CoreValve implant depth improved neo‐sinus washout ( p < .001). The 10% SAPIEN 3 under‐expansion improved neo‐sinus washout by 23% ( p < .001). Under‐expansion of both valve types caused higher pressure gradients and smaller effective orifice areas than full expansion. Conclusions: Neo‐sinus flow stasis is influenced by THV expansion and implant depth (CoreValve). The 10% valve under‐deployment (oversizing) may facilitate reduced flow stasis in the neo‐sinus with minimal increase in pressure gradients. This strategy may be helpful for patient anatomies, which are in‐between transcatheter valve sizes.